Synthesis of strigolactones, a strategic account - Zwanenburg, Binne; Ćavar Zeljković, Sanja; Pospíšil, Tomáš (Pest management science, 2016)
Strigolactones (SLs) constitute a new class of plant hormones that have received growing interest in recent years. They firstly became known as signalling molecules for host recognition by parasitic plants, and for symbiosis of plants with arbuscular mycorrhizal fungi. Furthermore, they are involved in numerous physiological processes in plants, such as the regulation of plant architecture and the response to abiotic factors. SLs are produced by plants in extremely low quantities, and they may be unstable during the purification process. Therefore, their total synthesis is highly relevant for confirming the structures assigned on the basis of spectroscopic and other physical data. A second important theme in SL research is the design and synthesis of SL analogues that have a simplified structure while still featuring the essential bioproperties. This review summarises the strategy and synthesis of naturally occurring SLs, and the design and synthesis of SL analogues with appreciable bioactivity.
Keywords: strigol; orobanchol; total synthesis; Plant Growth Regulators; GR24; Lactones; kontrola plevele; Weed Control; strigolactones; laktony; regulátory růstu rostlin; strigolactone analogues and mimics